Hydrothermal Preparation of Apatite-Type Phases La9.33Si6O26 and La9M1Si6O26.5 (M = Ca, Sr, Ba) - Atiek Rostika Noviyanti; Bambang Prijamboedi; I Nyoman Marsih; Ismunandar Ismu (Journal of Mathematical and Fundamental Sciences, 2012)
Apatite-type lanthanum silicates show a great potential to be used as an electrolyte for intermediate- to low-temperature (600-700 ï‚°C) solid oxide fuel cells (ITSOFC). However, so far these materials need to be prepared using a very high-temperature method, thus there is a growing interest to prepare apatites at lower temperatures. This paper reports the synthesis of undoped La9.33Si6O26 and doped apatites (La9CaSi6O26,5, La9SrSi6O26,5, and La9BaSi6O26,5) from raw materials La2O3, Na2SiO4, BaCO3, CaCO3, and SrCO3 using a hydrothermal method. The polycrystalline apatites were obtained as a white powder, after the basic solution of the reagent mixture was heated at 240 ï‚°C in an autoclave for 3 days. Le Bail refinement of the X-ray powder diffraction data showed that the compounds have a hexagonal cell (P 63/m space group). In this paper, the undoped La9.33Si6O26 and La-doped apatite ionic conductivities are also presented.